2014
DOI: 10.1155/2014/434239
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of the Polyherbal Formulation “ImmuPlus”: A Nutritional Supplement for Horses

Abstract: In order to counteract harmful effects of oxidative stress due to pathological conditions or physical exercise, horses are often administered dietary supplements having supposed high antioxidant activities. The aim of the present study was to identify the in vitro antioxidant potential of “ImmuPlus”, a polyherbal formulation (Global Herbs LTD, Chichester, West Sussex, Great Britain), containing three medicinal plants (Withania somnifera, Tinospora cordifolia, and Emblica officinalis), known in Ayurveda for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Tinospora cordifolia acts as an immunostimulant and it has been shown that its use decreases the incidence of disease and the use of antibiotics (Mukherjee et al 2010). The tocopherols, ascorbates and polyphenols within ImmuPlus could function as antioxidants and as immunostimulants (Ceccini et al 2014). Polyphenols are secondary plant metabolites and have been shown to exert antioxidative and antiinflammatory effects; this is important in domestic animals because of the oxidative stress conditions promoted by intensive systems; in addition, polyphenols provide protection against bacteria, viruses and fungi (Gessner et al 2017) The quadratic changes in segmented neutrophils could be the response to some polyherbal compounds but these counts are not correlated with the presence of bacterial disease (Honda et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tinospora cordifolia acts as an immunostimulant and it has been shown that its use decreases the incidence of disease and the use of antibiotics (Mukherjee et al 2010). The tocopherols, ascorbates and polyphenols within ImmuPlus could function as antioxidants and as immunostimulants (Ceccini et al 2014). Polyphenols are secondary plant metabolites and have been shown to exert antioxidative and antiinflammatory effects; this is important in domestic animals because of the oxidative stress conditions promoted by intensive systems; in addition, polyphenols provide protection against bacteria, viruses and fungi (Gessner et al 2017) The quadratic changes in segmented neutrophils could be the response to some polyherbal compounds but these counts are not correlated with the presence of bacterial disease (Honda et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Natural products with antioxidant activity have been recognized as valuable tools in the management of oxidative/nitrosative stress-induced pathologies [19]. Plants that contain certain amounts of polyphenols and flavonoids are perfect sources of antioxidants [20,21], but some studies infirmed this claim [22]. In other studies, the total phenolic content and flavonoid content did not correlate well with the results from the 1,1-diphenyl-2-picrylhydrazyl (DPPH) test.…”
Section: Pharmacological Studies 221 Total Antioxidant Capacitymentioning
confidence: 99%
“…The polyphenol content in forage was extracted with water as suggested by Cecchini et al (2014) with slight modifications. Briefly, 5 g of forage sample was extracted by soaking in 50 mL of water at room temperature (20°C) for 48 h under gentle shaking.…”
Section: Total Phenolic Content In Forage and Cheesementioning
confidence: 99%